Improve Students’ Skills in Listening Comprehension by Using Song Based on Multimedia - Hariratul Jannah; Abdollah Abdollah; Syahria Majid (Tamaddun Life, 2018)
In order to improve the quality of learning English, especially listening skills, students of the English Literature Study Program and the English Language Education Study Program submitted the research title "Improving the Skill of Student Multimedia Comprehension Listening Through Multimedia-Based Song Media." The specific objectives of this study were to: 1) improve listening skills in English-speaking students of the English Language and Literature Study Program at the Faculty of Letters of UMI; 2) developing listening learning models with multimedia-based song media. This research was conducted in the UMI English Literature and English Language Education Study Program at the Faculty of Letters with targeted results as follows: 1) in one year this was a valid draft model for learning listening with multimedia-based song media. The method used in this study is action research with a population of 156 students. This study produced a draft listening comprehension model, the results of the study showed that the learning process of Listening comprehension used multimedia-based songs with subtitles of positive student responses. From the questionnaire / questionnaire / close questionnaire shows ≥ 75% of students respond more easily and prefer the learning process to understand meaning and understand what is heard from native speakers in learning listening comprehension. This study recommends for listening lecturers to use songs as one of the media in learning that will improve student skills